Perception and Attitude about Utilization of Complementary and Alternative Medicine among Caregivers of the Mentally Challenged in Ebonyi State: A Cross-Sectional Study - Nwoke, Esther; Agbapuonwu , Noreen (Global Journal of Health Sciences, 2023)
Purpose: Mental health issues pose a great challenge to healthcare systems especially in developing countries, and having 35% global burden of sickness/disability, Nigeria shares 13% of it. Individuals, both the victims and relatives desperately try all they can to treat this condition. Informal caregivers including family members and friends play a major role in seeking help and choosing treatment regimen and most of them choose complementary and alternative medicine (CAM). CAM is popular in treating chronic illnesses including mental conditions in sub-Saharan African as stated by WHO. This study displayed both positive and negative perception and attitude of informal caregivers about CAM use for mental health challenges, characteristics of users, types and outcomes of use. Methodology: The study is a quantitative, cross sectional study carried out from 15th February to 15th of November 2022, using self-structured questionnaires. Of 389 questionnaires administered, 381 copies were returned and properly filled (97.5% response). The informal caregivers of the mentally challenged were recruited using convenience sampling method. The participants have mean age and standard deviation of 33.5+/- 8.6years, whose mentally challenged relatives had used CAM for the past 12 months and some current users. The questionnaires included information on socio-demographic data, perception and attitude about CAM use, types in use, and outcomes of use. SPSS versions 25, student test, ANOVA, among others, were used to compare perception and attitude about use of CAM and socio-demographic data of the caregivers. 92% participants confirmed that their mentally challenged relatives use some forms of CAM in treatment. The therapies used included herbal drugs, spiritual intervention, and alternative medical system (homeopathic medicine). Findings: The result revealed both positive and negative perception and attitude about CAM use and most caregivers could not identify any good effects of these therapies but still use them. The findings also showed that some socio-demographic factors affect CAM use. They noted that CAM use alone cannot cure, but also complicate mental illness. Unique Contribution to Theory, Practice and Policy: It was concluded that research on effectiveness and safety of each CAM will help improve mental healthcare.